2013
DOI: 10.52041/serj.v12i1.321
|View full text |Cite
|
Sign up to set email alerts
|

Worry, Intolerance of Uncertainty, and Statistics Anxiety

Abstract: Statistics anxiety is a problem for most graduate students. This study investigates the relationship between intolerance of uncertainty, worry, and statistics anxiety. Intolerance of uncertainty was significantly related to worry, and worry was significantly related to three types of statistics anxiety. Six types of statistics anxiety were significantly lower by the end of the semester. First published May 2013 at Statistics Education Graduate students ournal Archives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 40 publications
1
10
1
1
Order By: Relevance
“…Lastly, Mills found that many factors determine whether students’ attitudes toward statistics are either positive or negative, such as previous experiences with math or statistics, students’ self‐confidence, or teaching methods used in the statistics course 76 . Correlation data from the meta‐analysis supported the theorized bilateral relationship between the constructs; with positive attitudes toward statistics equating to lower levels of SA, and both negative attitudes and general negative affect acting as a predictor of SA 30,32,46,50 . Unfortunately, due to the small number of studies evaluating negative or positive attitudes, these were combined into a single score for analysis and no specific conclusions regarding these two types of attitudes (negative and positive) could be drawn.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Lastly, Mills found that many factors determine whether students’ attitudes toward statistics are either positive or negative, such as previous experiences with math or statistics, students’ self‐confidence, or teaching methods used in the statistics course 76 . Correlation data from the meta‐analysis supported the theorized bilateral relationship between the constructs; with positive attitudes toward statistics equating to lower levels of SA, and both negative attitudes and general negative affect acting as a predictor of SA 30,32,46,50 . Unfortunately, due to the small number of studies evaluating negative or positive attitudes, these were combined into a single score for analysis and no specific conclusions regarding these two types of attitudes (negative and positive) could be drawn.…”
Section: Discussionmentioning
confidence: 78%
“…Results on the role of this factor in SA indicate that students with lower rates of positive affect regarding statistics tended to present with higher levels of anxiety 44 . Also, SA correlated positively with the pathological traits of worry, intolerance of uncertainty, and coping strategy, while worry, perfectionism, and procrastination were found to be specific predictors of SA 15,32,45–49 . Furthermore, psychological flexibility and academic dishonesty also mediated the relationship between SA and statistics achievement 18,36 …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In general, worry is described as a negative chain of cognitions that represents an attempt at mental problem solving of an issue, whose outcome is unknown and (thus) has the possibility of being negative [ 31 ]. According to worry is stipulated by the anticipation of negative and uncertain outcomes [ 32 ], and in such, a state of emotions related to how one perceives the situation.…”
Section: Introductionmentioning
confidence: 99%